Economic report of the President : transmitted to the Congress, February, 1982 together with the annual report of the Council of Economic Advisers - United States President, Ronald Reagan; Council of Economic Advisers (U.S.). (Washington : United States Government Printing Office, 1982)
The book covers, Economic policy for the 1980s, government and the economy, monetary policy inflation and employment, federal budget issues, tax policy and economic growth, reforming government regulation of economic activity, and the United States in the international economic system.
rpm 15/05/2017
Loans
Keywords: United States -- Economic policy; United States -- Economic conditions -- 1971-; Economic history; Economic policy; United States